DIMENSI KUALITAS DAN HARGA SEBAGAI FAKTOR PENENTU KEPUASAN DAN LOYALITAS KONSUMEN - Ernawati & Untung Sriwidodo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT The relatively service-driven restaurant industry is becoming more important in generating income for many countries and hence the service performance of the restaurants must be well understood and managed. The key determinants for restaurant service quality need to be identified, especially for the important segment such as youth consumers. Therefore, this study aims to explore the importance of physical environment quality, human service, food quality and price from the youth consumer’s perspective. This study using 100 youth consumers in Waroeng "SS" Surakarta taken with snowball and convenience sampling techniques. Testing hypotheses formed by 3 regression model aims to analyze the key determinants of youth satisfaction and youth loyalty, and examined the effect of satisfaction to youth loyalty. Results of this study show that physical environment quality, human service, food quality, and price were all significant effect to youth satisfaction and youth loyalty, further satisfaction was significant effect to youth loyalty. Finally, the key determinants on youth satisfaction was mainly physical environment quality, while the key determinants on youth loyalty was mainly price. Keywords: physical environment quality, human service, food quality, price, youth satisfaction, youth loyalty